Applying UTAUT Model to Understand Use of Behavior Health Applications User in Indonesia During the COVID-19 - Gugun Geusan Akbar; Muchtar; Aji Abdul Wahid; Ikeu Kania; Annisa Deliana Putri; Dini Turipanam Alamanda (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
This study examines the adoption of the PeduliLindungi application during the COVID-19 pandemic in Indonesia using the UTAUT paradigm. The data was submitted by 200 users of the PeduliLindungi app. SEM-PLS was used to analyze the relationships between the variables and assess several hypotheses. To enlarge the scope of the investigation, Importance-Performance Map Analysis (IPMA) and Multi-Group Analysis (MGA) were also looked at as moderating variables. The findings revealed that facilitating settings had no discernible impact on how people use the PeduliLindungi application, whereas performance expectation, effort expectation, and social influence all positively affect behavioral intention and usage behavior. Second, the proposed model was not significantly impacted by gender, age, or educational attainment. Third, social influence is more significant in behavioral intention but less significant in use behavior components, performance expectation is more significant in use behavior, and effort expectancy is more prominent than other dimensions in behavioral intention. The contribution of this research is to provide a broader perspective in understanding the adoption of PeduliLindungi application so that it can convey a review of the policy implications for technology adoption in Indonesia.